Gas Chromatography-Mass Spectroscopy (GC-MS) Study of Endosulfan in Biological Samples - Sinha, S.N.; Patel, T.S.; Desai, N.M.; Mansuri, M.M.; Dewan, A.; Saiyed, H.N. (Asian Journal of Chemistry, 2016)
Mass spectrometry method has been used with capillary gas chromatography in electron ionization mode to identify the presence of α, β and endosulfan sulfate in human serum samples. The fragmentation ions were obtained due to ring cleavage, rearrangement and remote charge process. Solvent extraction procedure was used for isolation of compounds from serum sample. A detection limit as low as 100 ppb for α, β and sulfate could be easily achieved for confirmation. For endosulfan and sulfate the m/z values were obtained at intervals of M2+. The m/z values of α and β-endosulfan are identical but they differ in retention time. Therefore the spectra reported might serve as reference spectra for identification of different types of organo-chlorine pesticide (OCP) in human serum sample.